Essays in poverty and household analysis in Africa - Khan, Rumman (2017)
This thesis consists of three self-contained chapters on issues relating to the empirics of poverty and household analysis in Africa. The first analyses poverty at the country level, highlighting the diversity of experience in poverty reduction performance over the last few decades and assessing its causes. The other two studies are more methodological in their content, exploring how poverty and related issues can be analysed at the household level using existing survey data that pose difficulties as they do not track the same set of households over time.